Females with hip-related pain display altered lower limb mechanics compared to their healthy counterparts in a drop jump task. (December 2022) - Grosklos, Madeline; Lewis, Cara L; Jochimsen, Kate; Perry, Jennifer; Ellis, Thomas J; Vasileff, William K; Elwood, Megan; Di Stasi, Stephanie
Abstract: Background: Hip-related pain describes femoroacetabular impingement syndrome, acetabular dysplasia, and other hip pain conditions without clear morphological features. Movement strategies in this population, notably sex-related patterns, are poorly understood and may provide insights into why females report more pain and worse function. This study examined the sex-related differences during a drop vertical jump task between those with hip-related pain and healthy controls. Methods: Patients with hip-related pain and healthy controls completed five repetitions of a drop jump while their kinematics and kinetics were recorded using a motion capture system and force plates. Hip, knee, and ankle joint angles and external joint moments during landing were used in general estimating equations for comparison of group by sex by limb interactions. Time series data were further investigated using statistical parametric mapping. Findings: Females with hip-related pain had 9.1° less hip flexion ( P   =  .041) and 9.2° less knee flexion ( P   =  .024) than healthy females, and 8.3° less knee flexion than male counterparts with hip-related pain ( P   =  .039). Males demonstrated 1.4° less hip flexion on the affected side compared to their uninvolved side ( P   =  .004). Statistical parametric mapping results showed significant differences in knee flexion angle for females with hip-related pain compared to healthy females ( P   =  .042). There were no significant differences in hip, knee, or ankle moments. Interpretation: Females with hip-related pain showed kinematic patterns distinct from healthy controls. Sex may be an important variable of interest in characterizing movement impairments in this population and movement impairments may be an appropriate target for intervention for these patients. Highlights: Drop jump kinematics differ between those with hip pain and controls. Females with hip pain show less hip and knee flexion compared to female controls. Males with hip pain did not differ in kinematics from male controls. Sex-specific movement patterns exist in those with hip-related pain.